Matrix Certified Reference Materials - Tadeusz Gorewoda; Justyna Kostrzewa; Marta Wolska; Ewa Jamroz; Jacek Anyszkiewicz (Encyclopedia, 2025)
Matrix certified reference materials (mCRMs) are materials characterized by suitable homogeneity, stability, and traceability, with certified values, including uncertainties, and a specific matrix. mCRMs constitute a reference for instrumental analytical methods and ensure their metrological consistency. Matrix certified reference materials (mCRMs) are essential tools for ensuring the accuracy and traceability of analytical measurements, particularly for samples with complex matrices. These mCRMs are carefully manufactured materials that closely mimic the composition and properties of real samples, allowing laboratories to validate their analytical methods, calibrate analytical instruments, or check the classical methods. This article highlights the challenges associated with the production and characterization of these complex mCRMs, including obtaining homogeneous materials, establishing accurate target values, and ensuring stability for different types of materials, such as gases, liquids, and metal alloys. Additionally, the process of statistical evaluation through the use of advanced statistical methods is discussed, as is the systems approach associated with the implementation of the ISO 17034 standard, which specifies the requirements for manufacturers of reference materials. This paper also includes a summary of the current status in trends of normalization as well as mCRM production.